2016
DOI: 10.3389/fncel.2016.00154
|View full text |Cite
|
Sign up to set email alerts
|

Neuroserpin Differentiates Between Forms of Tissue Type Plasminogen Activator via pH Dependent Deacylation

Abstract: Tissue-type plasminogen activator (t-PA), initially characterized for its critical role in fibrinolysis, also has key functions in both physiologic and pathologic processes in the CNS. Neuroserpin (NSP) is a t-PA specific serine protease inhibitor (serpin) found almost exclusively in the CNS that regulates t-PA’s proteolytic activity and protects against t-PA mediated seizure propagation and blood–brain barrier disruption. This report demonstrates that NSP inhibition of t-PA varies profoundly as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Altering the RCL conformation by disruption of the salt bridge between residues R362 and E289 contributes to the fragility of the neuroserpin-tPA complex [ 30 ]. A detailed study has also shown that pH has an important role in substrate recognition and deacylation rates during neuroserpin’s inhibition of tPA, which is different between the single-chain and two-chain forms of tPA [ 40 ]. It should be noted that many of these studies have been performed using recombinant neuroserpin lacking N -glycans, but a recent report shows that N-glycosylation slightly improves the inhibitory activity of neuroserpin against tPA [ 41 ].…”
Section: Structure Function and Conformational Flexibility Of Neuroserpinmentioning
confidence: 99%
See 1 more Smart Citation
“…Altering the RCL conformation by disruption of the salt bridge between residues R362 and E289 contributes to the fragility of the neuroserpin-tPA complex [ 30 ]. A detailed study has also shown that pH has an important role in substrate recognition and deacylation rates during neuroserpin’s inhibition of tPA, which is different between the single-chain and two-chain forms of tPA [ 40 ]. It should be noted that many of these studies have been performed using recombinant neuroserpin lacking N -glycans, but a recent report shows that N-glycosylation slightly improves the inhibitory activity of neuroserpin against tPA [ 41 ].…”
Section: Structure Function and Conformational Flexibility Of Neuroserpinmentioning
confidence: 99%
“…This was indeed demonstrated in different in vitro studies showing complex formation and inhibition of the proteolytic activity of tissue-type plasminogen activator (tPA), and to a lesser extent of urokinase plasminogen activator (uPA), trypsin and plasmin [ 11 , 12 , 71 ]. Complex formation with tPA, but not with uPA, has been later demonstrated in vivo in the brain of rodents overexpressing neuroserpin [ 72 , 73 ], and recent work has shown that neuroserpin can discriminate between one- and two-chain tPA [ 40 ]. The serine protease tPA has a prominent role in the fibrinolytic cascade, where it activates plasminogen to plasmin, but it is also highly expressed in the CNS, with a pattern overlapping that of neuroserpin [ 18 , 74 ].…”
Section: Physiological Roles Of Neuroserpinmentioning
confidence: 99%
“…During the conformational change from the native to the RCL-cleaved form, a consistent stabilization of the serpin molecule takes place, yielding a cleaved form that is hyper-stable [11]. However, opposite to other serpin-protease pairs, the NS-tPA complex is short-living and rapidly dissociates at physiological pH, releasing free cleaved NS and active tPA [6,12,13]. Another serpin inhibitor of tPA, plasminogen activator inhibitor-1 (PAI1), is instead forming a long-living acyl-complex whose dissociation has never been observed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to PAI1, NS discriminates between tPA and uPA (urokinase-type plasminogen activator), and between the single-or double-chain tPA [12]. The pH also plays an important role in the stability of the NS-tPA complex [13]. Lee et al demonstrated that strands sC1 and sC2 and helices hCD and hE contribute to the recruitment of tPA and to the stabilization of the NS-tPA complex [14].…”
Section: Introductionmentioning
confidence: 99%